Validitas Tes Buatan Guru Bidang Studi Matematika Menurut Teori Tes Klasik Tingkat SMP di Kota Baubau - Rasmuin Rasmuin; Dinul Salam Azhari (Jurnal Akademik Pendidikan Matematika, 2022)
Objective of this research was to analysis and to describe the level of validity of the test madeby Mathematics teacher according to the Classical Test Theory at the Junior High School Level in Baubau City. This Research was a descriptive quantitative research. The subjects of this research were all multiple-choice tests made by the teacher for the final even-semester test for class VIII students in the 2020/2021 academic year in the field of mathematics subject at 7 state Junior High School in Baubau City. The Instruments in this research were student answer sheets, answer keys and recapitulation of student criteria at grade VIII. Data collection techiques used documentation techiques. Analysis of the data used was using the SPSS Statistic application version 26. Based on the results of the research, it could be concluded that, the results of the analysis of the validity of the test made by the teacher at SMP Negeri 1 Baubau of 0.684 which meant the validity was in the fairly good category, SMP Negeri 3 Baubau was 0.770 which meant the validity was in the good category, SMP Negeri 5 Baubau was 0.491 which meant the validity was in the good enough category, SMP Negeri 7 Baubau of 0.404 which meant the validity was included in the category of good enough, SMP Negeri 9 Baubau of 0.439 which meant the validity was in the category of good enough, SMP Negeri 11 Baubau of 0.434 which meant the validity was in the category of good enough, SMP Negeri 17 Baubau was 0.611 which meant that the validity was categorized as good enough. So that the validity of the test made by the teacher in the field of Mathematics Subject according to the Classical Test Theory at the Junior High level in Baubau City was 0.547 with the category of good enough.